Konsep Takhalluq bi Akhlaqillah sebagai Proses dan Hasil Pendidikan Islam - Giantomi Muhammad; Nurwadjah Ahmad Eq; Andewi Suhartini (Al-Fikr: Jurnal Pendidikan Islam, 2021)
The concept of takhalluq bi akhlaqillah as a process and outcome of Islamic education provides an idea in shaping a human personality with character. This concept comes from the teachings of Sufism which are exemplified by Sufis as a way to increase the level towards the love of Allah SWT. The purpose of this research is to find the concept of the process and outcomes of Islamic education with the concept of takhalluq bi akhlaqillah which is the basis for the implementation of the Islamic education process. The method used in this research is literature study and content analysis, followed by descriptive-analytic and the last step is descriptive analysis and data interpretation. The results of this study show that Islamic education in the concept of takhalluq bi akhlaqillah emphasizes the process of increasing the faith and devotion that teachers can do and efforts to internalize it in the Islamic education curriculum. Teachers and the Islamic education curriculum are the most important elements in conveying takhalluq bi akhlaqillah attitudes that form human personalities who can love Allah SWT to increase faith and devotion and lead to noble behavior.